Assessment of trace metals in seagrass areas of Merambong shoal in Johor, Malaysia - Sidi, Nordiani (2019)
Seagrass bed and estuarine ecosystems are essential to the environment. Nevertheless, due to the massive development surrounding Johor Straits, it causes the estuary ecosystem at risk, which can be harmful to the health of the aquatic ecosystem. Meanwhile, most of the established studies of seagrass found in Malaysia were subjected to the biology and ecology field. Therefore, there was a knowledge gap in terms of trace metals profiling in the seagrass ecosystem. Thus, it is imperative to assess the trace metals pollution in the seagrass vegetated area of Merambong shoal, which focused on the distribution, enrichment and metals mobility of trace metals in surface sediment, pore water, and seagrass. In addition, this study aims to provide the baseline data on the physicochemical characteristics of surface sediment and pore water as well as the current status of pollution levels in these environmental matrices. Other than that, this study also assessed the potential of Enhalus acoroides as a bioindicator of trace metals. In order to achieve these objectives, 60 samples of surface sediment and pore water were randomly collected from 20 sampling points, which covered Merambong shoal area. The sampling campaign was conducted in June 2014 during the low tide. E. acoroides complete with roots, rhizomes, and blades were collected at the same location as the surface sediment and pore water were sampled. The collected surface sediment and pore water were measured for in-situ parameters (pH, salinity, TDS (Total Dissolved Solids) and electrical conductivity (EC)). The surface sediment and pore water also were analysed for chemical analyses (i.e., organic matter, cation exchange capacity, major anions and cations). Surface sediment, pore water, and E. acoroides were digested using acid digestion method for trace metals concentrations measurement. The concentrations of trace metals (i.e., cadmium (Cd), copper (Cu), lead (Pb), nickel (Ni), and zinc (Zn)) in collected samples were analysed by the inductive coupled plasma mass spectrometry (ICP-MS). In general, the physicochemical parameters (pH, salinity and EC) of surface sediment and pore water, the domination of sodium (Na+) and chloride (Cl-) in pore water and exchangeable of Na+ in surface sediment were mainly influenced by the fresh seawater mixing condition from nearby streams and Johor Straits. The influence of salinity from seawater also contributes to the classification of pore water as sodium chloride waters. The mean concentration of trace metals in surface sediment was in the following order: Zn>Pb>Cu>Ni>Cd while for pore water was as follows: Cu>Ni>Zn>Pb>Cd. The mean trace metals concentrations of E. acoroides was in the order of Zn>Cu>Ni>Pb>Cd. The irregular tidal wave and seawater current are the factors affecting the metals distribution. The highest concentration of Zn in surface sediment and seagrass is due to Zn is relatively abundant in the environment, essential micronutrients for plants and input from the anthropogenic activities. As for Soil-Water Partition Coefficient (Kd), Pb has high Kd value indicating higher retention and less mobility because inorganic lead compounds are commonly abundant in the sediment and do not dissolve in water under natural conditions. The concentration of Cd, Cu, Ni, Pb, and Zn in the surface sediment samples were very in low range and did not exceed the sediment quality guidelines values (i.e., Hong Kong Interim Sediment Quality Value (HK ISQV) low, Australian and New Zealand Environment and Conservation Council (ANZECC), Interim Sediment Quality Guidelines (ISQG) low, National Oceanic and Atmospheric Administration (NOAA) low and National Oceanic and Atmospheric Administration (NOAA) Effects Range Median (ERM)). Based on assessment via indices (i.e., Enrichment Factor (EF), Geoaccumulation Index (Igeo), and Contamination Factor (CF)), Pb showed significant enrichment in the surface sediment of Merambong shoal. The enrichment of Pb influenced by anthropogenic activities related to shipping and cargo activities. The value for The Risk Factor (Eri) and Risk Index (RI) for surface sediment were <40 and <150. These ecological risk indices showed that the pollution and ecological risks of all trace metals were minimal. However, Interstitial Water Criterion Toxic Unit (IWCTU) revealed that all collected pore water samples could pose a risk of toxicity to overlying water, surface sediment, and aquatic organisms. The adverse environmental impacts that occur under sediment resuspension events lead to the toxicity of pore water in Merambong shoal. Bioconcentration Factor (BCF) revealed that E. acoroides have a significant ability to accumulate all studied trace metals from pore water. Each plant parts of E. acoroides showed different abilities in accumulating nutrients; blades showed the ability to accumulate more Cd and Ni while rhizomes for Zn and Cd, while roots for Pb. The biota-sediment accumulation factor (BSAF) suggested that E. acoroides were macroconcentrator of Cd, Cu, and Ni. Meanwhile, Translocation Factor (TF) revealed that E. acoroides is capable of translocating Cd, Cu, Ni, and Zn from roots to rhizomes and from roots to blades. E. acoroides control the translocation of Pb to the entire plant parts by isolate Pb in the roots to prevent growth inhibition and death. All of these suggested E. acoroides has potential as a bioindicator for Cd, Cu, Ni, and Zn, except for Pb. This study has successful provides a baseline of trace metals pollution status in the seagrass vegetated area. Through this study, the distribution and enrichment pattern of trace metals in surface sediment and toxicity of pore water also were further understood. This study also highlighted the potential of E. acoroides to be used as a bioindicator to reflect the trace metals pollution.